COGNITIVE-BEHAVIORAL MARITAL THERAPY: A COGNITIVE-BEHAVIORAL APPROACH FOR MARITAL DISTRESS - Sutarimah Ampuni (Faculty of Psychology Universitas Gadjah Mada, 2004)
Marriage therapy was initially developed in the United States in the 1930s. It was originally born by psychoanalysis, with the first report on psychoanalysis of married couples was presented in 1931 (Nichols & Schwartz, 1998). In recent years, there have been many other approaches being applied for marital problems, including classicapproaches such as experiential, insight-oriented, and behavioral approaches, and more contemporary approaches such as solution-building and cognitive-behavioral approaches.